Creating a Computer-Aided Teaching Tool for the History of Economic Thought - O'Donnell, Margaret G. (The Journal of economic education, 1991)
This article describes the development of a computer tutorial for use in a history of economic ideas class. An early version of the tutorial contained ten topics, ranging from early Mercantilist thought to Jevons's marginal utility analysis. These concepts were presented in three ways: verbally, graphically, and in summary form. Student critiques were used to extend the content and revise the mode of presentation.